Political Violence and Radicalization in the North- Eastern Nigeria: Analyzing the Youth Bulge Phenomenon (Journal of Governance and Development (JGD), 2023)
Political Violence has recently become a recurring decimal in NorthernNigeria especially in the North-Eastern part of the country where peaceseems to have eluded the region since 2009. Several scholarly inputs werepropounded in an attempt to address and find a lasting solution to thepersistent incidence of violence ravaging the region. This article is anotherattempt geared toward addressing the problem by looking at it from a differentperspective that is the youth Bulge Phenomenon. It is the conception of thispaper that, the genesis, the life span and the demise of political violence isgreatly influence by the socio-cultural and political environment surroundingit. To understand political violence and the factors that breed it, one has tounderstand the environment that actually nurtured it. In other words, withoutunderstanding the socio-political attributes of a given population, one will notunderstand the causes of insurgency within it. This paper views environmentas a key factor in understanding the political violence within the context ofthe North-Eastern Nigeria. It examines environment from a demographicparlance and adopts the youth Bulge theory and the social identity theory toconceptually analyse the key elements that continue to shape and mould thegrowth of political violence in the North-Eastern Nigeria, where institutionalweakness due to poor governance, social categorization and the formationof social network were discovered to be the contributing factors to themenace.